Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

Adapting building stock archetype methodology for greenhouse stock characterisation - Junior Zannou; Danielle Monfet; Gilbert Larochelle Martin; Didier Haillot (Energy and Buildings, 2026)

Assessing the effects of thermo-oxidation and naturally-occurring trace metal ions on the peroxidative susceptibilities of unrefined and refined sunflower oils: An 1H NMR-coupled chemometrics study - Gilbert Ampem; Adam Le Gresley; Martin Grootveld; Simon De Mars; Declan P. Naughton (Food Research International, 2025)

Coral reef boulders as recorders of cyclone activity over the last 3500 years (Fakarava Atoll, Tuamotu, French Polynesia) - Lucien F. Montaggioni; Bernard Salvat; Éric Brunaud; Edwige Pons-Branchu; Gilbert Poli; Bertrand Martin-Garin (Marine Geology, 2025)

Potential of peatlands restoration for GHG emissions mitigation in France: Investigation of acquisition costs - Lise Pinault; Daniel Gilbert; Elsa Martin (Land Use Policy, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Dephasing of islet building between leeward and windward reef-rim sides, Bora Bora Island, Society Archipelago, central South Pacific - Lucien F. Montaggioni; Bernard Salvat; Edwige Pons-Branchu; Bertrand Martin-Garin; Gilbert Poli; Marie-Thérèse Vénec-Peyré; David Lecchini; Gaston Tong Sang (Quaternary International, 2025)

Invasive Buffelgrass, Cenchrus ciliaris , Balances Opportunistic Acquisition of Foliar fungi With Host and Environmental Filtering in Its Introduced Range - Elizabeth A. Bowman; Christine V. Hawkes; Nathan Jones; Robert M. Plowes; Dino J. Martins; Lawrence E. Gilbert (Molecular Ecology, 2025)
Plants host diverse assemblages of fungi on their foliar tissues, both in internal compartments and on exterior surfaces. When plant distributions shift, they can move with their fungal associates (i.e., co‐introduction) or acquire new associates present in the novel environment (host‐jumping). The fungal communities that plants acquire influence a plant's ability to establish and spread in this new environment. Here, we aimed to assess whether invasive C. ciliaris hosts similar groups of fungi in its native and introduced ranges and to evaluate community overlap of fungi associated with foliar tissue of C. ciliaris and native and non‐native plants within the introduced range. In the introduced range, the majority of OTUs associated with C. ciliaris were not found in its native range, although 3.2% of OTUs were common to both ranges. Of these shared OTU, 77.6% were found on co‐occurring natives and non‐natives in the introduced range, whereas 22.4% were unique to C. ciliaris indicating a possible co‐introduction. Fungal communities within the introduced range contained a higher proportion of generalist symbionts and increased heterogeneity of foliar communities than in its native range. Within the introduced range, host phylogenetic distance explained more variation than native status. Our findings provide evidence that non‐natives acquire fungi opportunistically from their environment, although host and environmental filtering is present suggesting that successful invasive plants may be able to limit the effect of poor symbionts and select for better ones. Future experimental work will be needed to confirm the occurrence of host selection and identify its mechanisms.

Vaccination of endangered wildlife as a conservation tool: Hindsights and new horizons in the pandemic era - Frances M.D. Gulland; Michelle Barbieri; Sarah Cleaveland; Martin Gilbert; Ailsa J. Hall; Tonie E. Rocke (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Petrogenesis of cassiterite-rich greisens from Guengue hill, Mayo Darlé, Northwestern Cameroon - Pemha Nyemb Sayom; Bravo Martin Mbang Bonda; Bayiga Elie Constantin; Mbai Simon Joel; Ngon Ngon Gilbert François; Nono Foudje Romaric Noël; Essono Eric; Etame Jacques (Ore and Energy Resource Geology, 2024)

Comparison of EnergyPlus inside surfaces convective heat transfer coefficients algorithms for energy modelling of high-density controlled environment agriculture - Gilbert Larochelle Martin; Danielle Monfet (Energy and Buildings, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Effectiveness of different antioxidants in suppressing the evolution of thermally induced peroxidation products in hemp seed oil - Gilbert Ampem; Adam Le Gresley; Martin Grootveld; Declan Patrick Naughton (Food Research International, 2024)

Laser ablation (in situ) Lu-Hf geochronology of epidote group minerals - Jie Yu; Stijn Glorie; Martin Hand; Alexander Simpson; Sarah Gilbert; Kristoffer Szilas; Nick Roberts; Mark Pawley; Yanbo Cheng (Contributions to Mineralogy and Petrology, 2024)
Epidote group minerals, including allanite, clinozoisite and epidote are common in a range of metamorphic, igneous and hydrothermal systems, and are stable across a wide range of pressure – temperature ( P–T ) conditions. These minerals can incorporate substantial amounts of rare earth elements (REEs) during their crystallisation, making them potential candidates for Lu–Hf geochronology to provide age constraints on various geological processes. Here we report on a first exploration into the feasibility of in situ Lu–Hf geochronology for epidote group minerals from various geological settings and compare the results with age constraints from other geochronometers. Magmatic allanite samples from pegmatites and monzogranites in the Greenland anorthosite complex, Coompana Province and Qingling Orogen provided dates consistent with magmatic events spanning from c. 2660 to 1171 Ma. In the Qingling pegmatites, a younger phase of hydrothermal allanite was dated at c. 215 Ma, consistent with the timing of regional REE mineralisation. Allanite from the Yambah Shear Zone, Strangways Metamorphic Complex, yielded Lu–Hf age of c. 430 Ma. It predates the garnet and apatite growth at c. 380 Ma, suggesting the Lu–Hf system can be preserved in allanite during prograde amphibolite-facies metamorphism. Additionally, Lu–Hf dates for hydrothermal clinozoisite and epidote are consistent with the timing of hydrothermal alteration and mineralisation in a range of settings, demonstrating the utility of the technique for mineral exploration. Despite the current lack of matrix-matched reference materials, the successful application of laser ablation Lu–Hf geochronology to epidote group minerals offers valuable geochronological insights into various geological processes that can be difficult to access through other geochronometers.

Field-scale efficacy of entomopathogenic nematodes to control false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), in citrus orchards in South Africa - Sean D. Moore; Ralf-Udo Ehlers; Aruna Manrakhan; Martin Gilbert; Wayne Kirkman; John-Henry Daneel; Jeanne Y. De Waal; Rynhardt Nel; Guy Sutton; Antoinette P. Malan (Crop Protection, 2024)

Testing the reproducibility of in situ Lu Hf dating using Lu-rich garnet from the Tørdal pegmatites, southern Norway - Stijn Glorie; Alexander Simpson; Sarah E. Gilbert; Martin Hand; Axel B. Müller (Chemical Geology, 2024)

Maize yield under a changing climate in Uganda: long-term impacts for climate smart agriculture - Alex Zizinga; Jackson-Gilbert Majaliwa Mwanjalolo; Britta Tietjen; Minella Alves Martins; Bobe Bedadi (Regional Environmental Change, 2024)

Potential Use of the Bakari (Adamawa–Cameroon) Quartzites as Sand Filters - Gilbert François Ngon Ngon; Michele Tatiana Minkoe; Zenon Itiga; Darman Japhet Taypondou; Oumar Oumla Kankao; Joel Simon Mbaï; Bravo Martin Mbang Bonda (Geotechnical and Geological Engineering, 2024)

Geochemical landscapes as drivers of wildlife reproductive success: Insights from a high-Arctic ecosystem - Floris M. van Beest; Niels Martin Schmidt; Lærke Stewart; Lars H. Hansen; Anders Michelsen; Jesper B. Mosbacher; Hugo Gilbert; Gaël Le Roux; Sophia V. Hansson (Science of The Total Environment, 2023)

Garnet Lu-Hf speed dating: A novel method to rapidly resolve polymetamorphic histories - Alexander Simpson; Stijn Glorie; Martin Hand; Carl Spandler; Sarah Gilbert (Gondwana Research, 2023)

Genomic diversity and differentiation between island and mainland populations of white‐tailed eagles ( Haliaeetus albicilla ) - Charles Christian Riis Hansen; Áki Jarl Láruson; Jacob Agerbo Rasmussen; Jesus Adrian Chimal Ballesteros; Mikkel‐Holger S. Sinding; Gunnar T. Hallgrimsson; Menja von Schmalensee; Robert A. Stefansson; Kristinn Haukur Skarphédinsson; Aili Lage Labansen; Madis Leivits; Christian Sonne; et al. (Molecular Ecology, 2023)
Divergence in the face of high dispersal capabilities is a documented but poorly understood phenomenon. The white‐tailed eagle ( Haliaeetus albicilla ) has a large geographic dispersal capability and should theoretically be able to maintain genetic homogeneity across its dispersal range. However, following analysis of the genomic variation of white‐tailed eagles, from both historical and contemporary samples, clear signatures of ancient biogeographic substructure across Europe and the North‐East Atlantic is observed. The greatest genomic differentiation was observed between island (Greenland and Iceland) and mainland (Denmark, Norway and Estonia) populations. The two island populations share a common ancestry from a single mainland population, distinct from the other sampled mainland populations, and despite the potential for high connectivity between Iceland and Greenland they are well separated from each other and are characterized by inbreeding and little variation. Temporal differences also highlight a pattern of regional populations persisting despite the potential for admixture. All sampled populations generally showed a decline in effective population size over time, which may have been shaped by four historical events: (1) Isolation of refugia during the last glacial period 110–115,000 years ago, (2) population divergence following the colonization of the deglaciated areas ~10,000 years ago, (3) human population expansion, which led to the settlement in Iceland ~1100 years ago, and (4) human persecution and exposure to toxic pollutants during the last two centuries.

Evaluation of phosphorus runoff from sandy soils under conservation tillage with surface broadcasted recovered phosphates - Clement D.D. Sohoulande; Ariel A. Szogi; Kenneth C. Stone; Gilbert C. Sigua; Jerry H. Martin; Paul D. Shumaker; Phil J. Bauer (Journal of Environmental Management, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The dilemma of Guinea grass (Megathyrsus maximus): a valued pasture grass and a highly invasive species - Aaron C. Rhodes; Robert M. Plowes; John A. Goolsby; John F. Gaskin; Boaz Musyoka; Paul-André Calatayud; Massimo Cristofaro; Eric D. Grahmann; Dino J. Martins; Lawrence E. Gilbert (Biological Invasions, 2021)

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Shrinking into the big city: influence of genetic and environmental factors on urban dragon lizard morphology and performance capacity - James Baxter-Gilbert; Julia L. Riley; Celine H. Frère; Martin J. Whiting (Urban Ecosystems, 2021)

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams - Magdalena Nagler; Nadine Praeg; Georg H. Niedrist; Katrin Attermeyer; Núria Catalán; Francesca Pilotto; Catherine Gutmann Roberts; Christoph Bors; Stefano Fenoglio; Miriam Colls; Sophie Cauvy‐Fraunié; Brian Doyle; et al. (Journal of Biogeography, 2021)
Aim Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon Methanogenic archaea and methane‐oxidizing microorganisms. Methods To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae , Methanosarcinaceae and Methanobacteriaceae , but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae , Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Modelling Eurasian beaver foraging habitat and dam suitability, for predicting the location and number of dams throughout catchments in Great Britain - Hugh A. Graham; Alan Puttock; William W. Macfarlane; Joseph M. Wheaton; Jordan T. Gilbert; Róisín Campbell-Palmer; Mark Elliott; Martin J. Gaywood; Karen Anderson; Richard E. Brazier (European Journal of Wildlife Research, 2020)
Eurasian beaver ( Castor fiber ) populations are expanding across Europe. Depending on location, beaver dams bring multiple benefits and/or require management. Using nationally available data, we developed: a Beaver Forage Index (BFI), identifying beaver foraging habitat, and a Beaver Dam Capacity (BDC) model, classifying suitability of river reaches for dam construction, to estimate location and number of dams at catchment scales. Models were executed across three catchments, in Great Britain (GB), containing beaver. An area of 6747 km 2 was analysed for BFI and 16,739 km of stream for BDC. Field surveys identified 258 km of channel containing beaver activity and 89 dams, providing data to test predictions. Models were evaluated using a categorical binomial Bayesian framework to calculate probability of foraging and dam construction. BFI and BDC models successfully categorised the use of reaches for foraging and damming, with higher scoring reaches being preferred. Highest scoring categories were ca. 31 and 79 times more likely to be used than the lowest for foraging and damming respectively. Zero-inflated negative binomial regression showed that modelled dam capacity was significantly related ( p = 0.01) to observed damming and was used to predict numbers of dams that may occur. Estimated densities of dams, averaged across each catchment, ranged from 0.4 to 1.6 dams/km, though local densities may be up to 30 dams/km. These models provide fundamental information describing the distribution of beaver foraging habitat, where dams may be constructed and how many may occur. This supports the development of policy and management concerning the reintroduction and recolonisation of beaver.

Bold New World: urbanization promotes an innate behavioral trait in a lizard - James Baxter-Gilbert; Julia L. Riley; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Runners and fighters: clutch effects and body size drive innate antipredator behaviour in hatchling lizards - James Baxter-Gilbert; Julia L. Riley; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2018)

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Tropospheric circulation during the early twentieth century Arctic warming - Martin Wegmann; Stefan Brönnimann; Gilbert P. Compo (Climate Dynamics, 2017)

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

Controls on Nitrous Oxide Production in, and Fluxes from a Coastal Aquifer in Long Island, NY, USA - Caitlin Young; Jonathan Martin; Gilbert Hanson (Journal of Marine Science and Engineering, 2016)
Nitrous oxide (N2O) has 265 times greater greenhouse potential than carbon dioxide and its atmospheric concentration has increased by about 20% since industrialization; however, N2O production and emissions from aquatic systems are poorly constrained. To evaluate N2O fluxes associated with meteoric groundwater discharge to coastal zones, we measured N2O concentrations in May and October 2011 from two discharge points of the Upper Glacial aquifer on Long Island, NY, USA. One coastal zone contains only fresh water and the other contains an upper saline zone. N2O concentrations decreased by around 40% for the fresh water and a factor of two for the salt water from May to October, 2011. Fluxes were around 100 to 200 times greater from the freshwater (246 to 448 µmol/m shoreline/day) than saltwater aquifer (26.1 to 26.5 µmol/m shoreline/day). N2O concentrations correlate positively with NO3− and dissolved oxygen concentrations and negatively with salinity, dissolved organic carbon (DOC) and N2 denitrification concentrations. The smaller saltwater N2O export resulted from DOC enrichment in the upper saline zone, which appears to have driven denitrification to completion, removed N2O, and increased N2 denitrification. DOC concentrations should be considered in global N2O flux estimates for coastal aquifers.

A fuzzy model to assess disaster risk reduction maturity level based on the Hyogo Framework for Action - Paulo Victor Rodrigues de Carvalho; Cláudio Henrique dos Santos Grecco; Armando Martins de Souza; Gilbert Jacob Huber; Jose Orlando Gomes (Natural Hazards, 2016)

First recorded case of tiger killing Eurasian lynx - Yuri K. Petrunenko; Ivan L. Polkovnikov; Martin Gilbert; Dale G. Miquelle (European Journal of Wildlife Research, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - David C. Watson; Warren W. Wakarchuk; Christian Gervais; Yves Durocher; Anna Robotham; Steve M. Fernandes; Ronald L. Schnaar; N. Martin Young; Michel Gilbert (Glycoconjugate Journal, 2015)

Farewell Wilfred - Ken Timmis; Michi Wagner; Juan Luis Ramos; Mike Jetten; Victoria Orphan; Martin Polz; Paola Bonfante; Jack Gilbert; Rachel Whitaker; Tom Wood; Jay Lennon; Volker Müller; et al. (Environmental Microbiology, 2015)

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Historical anthropogenic disturbances influence patterns of non-native earthworm and plant invasions in a temperate primary forest - Robin Beauséjour; I. Tanya Handa; Martin J. Lechowicz; Benjamin Gilbert; Mark Vellend (Biological Invasions, 2015)

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

Herbarium specimens reveal a historical shift in phylogeographic structure of common ragweed during native range disturbance - Michael D. Martin; Elizabeth A. Zimmer; Morten T. Olsen; Andrew D. Foote; M. Thomas P. Gilbert; Grace S. Brush (Molecular Ecology, 2014)
Invasive plants provide ample opportunity to study evolutionary shifts that occur after introduction to novel environments. However, although genetic characters pre‐dating introduction can be important determinants of later success, large‐scale investigations of historical genetic structure have not been feasible. Common ragweed ( A mbrosia artemisiifolia L .) is an invasive weed native to N orth A merica that is known for its allergenic pollen. Palynological records from sediment cores indicate that this species was uncommon before E uropean colonization of N orth A merica, and ragweed populations expanded rapidly as settlers deforested the landscape on a massive scale, later becoming an aggressive invasive with populations established globally. Towards a direct comparison of genetic structure now and during intense anthropogenic disturbance of the late 19th century, we sampled 45 natural populations of common ragweed across its native range as well as historical herbarium specimens collected up to 140 years ago. Bayesian clustering analyses of 453 modern and 473 historical samples genotyped at three chloroplast spacer regions and six nuclear microsatellite loci reveal that historical ragweed's spatial genetic structure mirrors both the palaeo‐record of A mbrosia pollen deposition and the historical pattern of agricultural density across the landscape. Furthermore, for unknown reasons, this spatial genetic pattern has changed substantially in the intervening years. Following on previous work relating morphology and genetic expression between plants collected from eastern N orth A merica and W estern E urope, we speculate that the cluster associated with humans’ rapid transformation of the landscape is a likely source of these aggressive invasive populations.

Associations of circulating retinol, vitamin E, and 1,25-dihydroxyvitamin D with prostate cancer diagnosis, stage, and grade - Rebecca Gilbert; Chris Metcalfe; William D. Fraser; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Richard M. Martin (Cancer Causes & Control, 2012)

A multi-data set comparison of the vertical structure of temperature variability and change over the Arctic during the past 100 years - Stefan Brönnimann; Andrea N. Grant; Gilbert P. Compo; Tracy Ewen; Thomas Griesser; Andreas M. Fischer; Martin Schraner; Alexander Stickler (Climate Dynamics, 2012)

Beware of the commercialization of human cells and tissues: situation in the European Union - Jean-Paul Pirnay; Alain Vanderkelen; Nadine Ectors; Christian Delloye; Denis Dufrane; Etienne Baudoux; Michel Van Brussel; Michael P. Casaer; Daniel De Vos; Jean-Pierre Draye; Thomas Rose; Serge Jennes; et al. (Cell and Tissue Banking, 2012)

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Predictors of 25-hydroxyvitamin D and its association with risk factors for prostate cancer: evidence from the Prostate testing for cancer and Treatment study - Rebecca Gilbert; Richard M. Martin; William D. Fraser; Sarah Lewis; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Chris Metcalfe (Cancer Causes & Control, 2012)

The Phage Therapy Paradigm: Prêt-à-Porter or Sur-mesure? - Jean-Paul Pirnay; Daniel De Vos; Gilbert Verbeken; Maia Merabishvili; Nina Chanishvili; Mario Vaneechoutte; Martin Zizi; Geert Laire; Rob Lavigne; Isabelle Huys; Guy Van den Mooter; Angus Buckling; et al. (Pharmaceutical Research, 2011)

Associations of circulating and dietary vitamin D with prostate cancer risk: a systematic review and dose–response meta-analysis - Rebecca Gilbert; Richard M. Martin; Rebecca Beynon; Ross Harris; Jelena Savovic; Luisa Zuccolo; Geertruida E. Bekkering; William D. Fraser; Jonathan A. C. Sterne; Chris Metcalfe (Cancer Causes & Control, 2011)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

Environmental Radioxenon Levels in Europe: a Comprehensive Overview - Paul R. J. Saey; Clemens Schlosser; Pascal Achim; Matthias Auer; Anders Axelsson; Andreas Becker; Xavier Blanchard; Guy Brachet; Luis Cella; Lars-Erik De Geer; Martin B. Kalinowski; Gilbert Le Petit; et al. (Pure and Applied Geophysics, 2010)

Variants in toll-like receptors 2 and 9 influence susceptibility to pulmonary tuberculosis in Caucasians, African-Americans, and West Africans - Digna Rosa Velez; Christian Wejse; Martin E. Stryjewski; Eduardo Abbate; William F. Hulme; Jamie L. Myers; Rosa Estevan; Sara G. Patillo; Rikke Olesen; Alessandra Tacconelli; Giorgio Sirugo; John R. Gilbert; et al. (Human Genetics, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

AtGRP5, a vacuole-located glycine-rich protein involved in cell elongation - Amanda Mangeon; Claudia Magioli; Adriana Dias Menezes-Salgueiro; Vanessa Cardeal; Cristina de Oliveira; Vinícius Costa Galvão; Rogério Margis; Gilbert Engler; Gilberto Sachetto-Martins (Planta, 2009)

A systemic approach for the development of FHB resistant germplasm accelerates genetic progress - A. Comeau; F. Langevin; V. Caetano; S. Haber; M. Savard; H. Voldeng; G. Fedak; Y. Dion; S. Rioux; J. Gilbert; D. Somers; R. Martin (Cereal Research Communications, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

AtGRP2, a cold-induced nucleo-cytoplasmic RNA-binding protein, has a role in flower and seed development - Adriana Flores Fusaro; Silvia Nora Bocca; Rose Lucia Braz Ramos; Rosa Maria Barrôco; Claudia Magioli; Vanessa Cardeal Jorge; Tatiana Cardoso Coutinho; Camila Martins Rangel-Lima; Riet De Rycke; Dirk Inzé; Gilbert Engler; Gilberto Sachetto-Martins (Planta, 2007)

Sex steroid receptor evolution and signalling in aquatic invertebrates - Heinz-R. Köhler; Werner Kloas; Martin Schirling; Ilka Lutz; Anna L. Reye; Jan-S. Langen; Rita Triebskorn; Roland Nagel; Gilbert Schönfelder (Ecotoxicology, 2007)

Evaluating Neanderthal Genetics and Phylogeny - Martin B. Hebsgaard; Carsten Wiuf; M. Thomas P. Gilbert; Henrik Glenner; Eske Willerslev (Journal of Molecular Evolution, 2007)

Education in sustainable production in US universities - Gilbert L. Rochon; Loring F. Nies; Chad T. Jafvert; Julie A. Stuart; Rabi H. Mohtar; Joseph Quansah; Akilah Martin (Clean Technologies and Environmental Policy, 2006)

Cumulative and Residual Effects of Repeated Sewage Sludge Applications: Forage Productivity and Soil Quality Implications in South Florida, USA (9 pp) - Gilbert Sigua; Martin Adjei; Jack Rechcigl (Environmental Science and Pollution Research, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Inhibition of HER-2 by three independent targeting strategies increases paclitaxel resistance of SKOV-3 ovarian carcinoma cells - Shaker Abuharbeid; Jrgen Apel; Gerhard Zugmaier; Cornelius Knabbe; Martin Sander; Sandra Gilbert; Frank Czubayko; Achim Aigner (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Erratum to: Transgenic rats expressing the human ET-2 gene: a model for the study of endothelin actions in vivo - Lutz Liefeldt; Gilbert Schönfelder; Wolfgang Böcker; Berthold Hocher; Chris E. Talsness; Rainer Rettig; Martin Paul (Journal of Molecular Medicine, 1999)

Transgenic rats expressing the human ET-2 gene: a model for the study of endothelin actions in vivo - Lutz Liefeldt; Gilbert Schönfelder; Wolfgang Böcker; Berthold Hocher; Chris E. Talsness; Rainer Rettig; Martin Paul (Journal of Molecular Medicine, 1999)

The Mouse Spam1 maps to proximal Chromosome 6 and is a candidate for the sperm dysfunction in Rb(6.16)24Lub and Rb(6.15)lAld heterozygotes - Xiangning Deng; Jennifer Moran; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Paul Primakoff; Patricia A. Martin-DeLeon (Mammalian Genome, 1997)

Potato notes - C. Tice; A. J. Johnston; E. P. Miller; E. A. Stokdyk; J. W. Weston; A. G. Tolass; J. Norton Woodruff; Ellwood Douglass; Wm. H. Martin; W. S. Blair; N. W. Glines; J. Tucker; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)